A Biomimetic Voltage‐Gated Chloride Nanochannel. Issue 16 (24th February 2016) - Liu, Qian; Wen, Liping; Xiao, Kai; Lu, Heng; Zhang, Zhen; Xie, Ganhua; Kong, Xiang‐Yu; Bo, Zhishan; Jiang, Lei
Abstract : A novel biomimetic voltage‐gated chloride nanochannel is described. This artificial nanochannel can realize reversible switching between the "on" and "off" states upon addition and removal of Cl − and can realize the selective and directional transport of Cl − driven by voltage. Moreover, it also has high sensitivity, good selectivity, responsive switchability, and good stability.